2007
DOI: 10.1111/j.1600-0447.2007.01095.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical illness and schizophrenia: a review of the literature

Abstract: Sartorius N. Physical illness and schizophrenia: a review of the literature.Objective: The lifespan of people with schizophrenia is shortened compared to the general population. We reviewed the literature on comorbid physical diseases in schizophrenia to provide a basis for initiatives to fight this unacceptable situation. Method: We searched MEDLINE (1966( -May 2006 combining the MeSH term of schizophrenia with the 23 MeSH terms of general physical disease categories to identify relevant epidemiological stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
358
3
24

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 560 publications
(407 citation statements)
references
References 248 publications
13
358
3
24
Order By: Relevance
“…Cancer is a leading cause of death worldwide, accounting for approximately 13% of all deaths in 2007 (WHO 2009). Some studies have reported an increased incidence of cancer in people with SMI, although data are conflicting (Howard 2010;Leucht 2007). This may be due to lack of consideration by researchers of the influence of missing cancer diagnoses, shortened life expectancy, historical and health service contexts, behavioural risk factors and genetic or drug effects (Howard 2010).…”
Section: B a C K G R O U N D Description Of The Conditionmentioning
confidence: 93%
“…Cancer is a leading cause of death worldwide, accounting for approximately 13% of all deaths in 2007 (WHO 2009). Some studies have reported an increased incidence of cancer in people with SMI, although data are conflicting (Howard 2010;Leucht 2007). This may be due to lack of consideration by researchers of the influence of missing cancer diagnoses, shortened life expectancy, historical and health service contexts, behavioural risk factors and genetic or drug effects (Howard 2010).…”
Section: B a C K G R O U N D Description Of The Conditionmentioning
confidence: 93%
“…Schizophrenia is one of the most stigmatized psychiatric diagnoses, and the increased frequency of physical diseases among individuals diagnosed with schizophrenia might be related to the unsatisfactory organization of health services, attitudes of medical personnel and the social stigma attributed to people with such a diagnosis in society (Leucht, Burkard, & Henderson et al, 2007). Three different types of stigma have been identified as barriers to healthy living; structural stigma, social stigma and self-stigma (Graham, Griffiths, & Tillotson et al, 2013).…”
Section: Master’s Level Mental Health Nursing Competencies In Terms Omentioning
confidence: 99%
“…Schizophrenia (SCZ) is a severe neuropsychiatric disorder with a lifetime prevalence of ~1% worldwide [1] . Clinically, SCZ is characterized by symptoms traditionally classifi ed as positive (delusions and hallucinations), negative (fl attened emotions and social withdrawal), and impairments of cognitive functions [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%